2015
DOI: 10.1186/s12875-015-0232-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of asthma care under different primary care models in Canada: a population-based study

Abstract: BackgroundPrevious research has shown variations in quality of care and patient outcomes under different primary care models. The objective of this study was to use previously validated, evidence-based performance indicators to measure quality of asthma care over time and to compare quality of care between different primary care models.MethodsData were obtained for years 2006 to 2010 from the Ontario Asthma Surveillance Information System, which uses health administrative databases to track individuals with as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The majority of patients were treated in primary health clinics, and only 5% of the patients were treated in tertiary hospitals. Although PFT and ICS are the most important diagnostic and treatment methods, respectively, only 23.47% of patients with asthma were assessed with PFT, and 25.37% of patients were treated Results of earlier studies correspond with those of the present study, which reported low PFT rates in the asthma population; however, these studies have reported a higher rate than that in the present study (11,(14)(15)(16). A population-based study in Canada revealed that the PFT rate improved from 2006 to 2010 at both the initial diagnosis (46.8% to 52.5%) and during monitoring (16.4% to 19.1%) (11).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The majority of patients were treated in primary health clinics, and only 5% of the patients were treated in tertiary hospitals. Although PFT and ICS are the most important diagnostic and treatment methods, respectively, only 23.47% of patients with asthma were assessed with PFT, and 25.37% of patients were treated Results of earlier studies correspond with those of the present study, which reported low PFT rates in the asthma population; however, these studies have reported a higher rate than that in the present study (11,(14)(15)(16). A population-based study in Canada revealed that the PFT rate improved from 2006 to 2010 at both the initial diagnosis (46.8% to 52.5%) and during monitoring (16.4% to 19.1%) (11).…”
Section: Discussionsupporting
confidence: 82%
“…Only 13% of Asia-Pacific patients with asthma in the 2003 Asthma Insights and Reality in Asia-Pacific (AIRIAP) study were prescribed an ICS (12). In a Canadian study, researchers reported that the ICS prescription rate increased from 2006 to 2010 (72.9% to 76.6%) (11). In addition, ICS therapy was used by 38.4% of patients with asthma in the GEDA study, and younger patients had a lower prescription rate (31.6% vs. 50.3%) (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion of spirometry in the assessment guarantees more accurate monitoring of asthma control [38][39][40][41] without input from secondary care 43 . Objective lung function measurements are not comprehensively used in asthma diagnostics 44 and monitoring 2,3,45 , despite several studies [38][39][40][41] and guidelines 1 supporting their use. A Swedish study showed that one third of the patients with asthma visiting PHC during initial visits and approximately half of the patients during follow-up visits had a clinical evaluation, including spirometry or peak flow monitoring, in agreement with recommendations 2 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, an accurate asthma diagnosis with pulmonary function testing and then proper treatment and general practitioner follow-up can lead to less ED visits, hospitalizations, time off-work, impaired lung function and mortality which could translate into cost savings in the long term. Descriptive epidemiological studies that can accurately identify the burden of chronic disease such as asthma are important for disease monitoring over time, resource allocation and measuring the effectiveness of interventions 34 .…”
Section: Practical Applications Of Epidemiologic Studiesmentioning
confidence: 99%